Treatment of symptomatic oral lichen planus (OLP) with 0.1% tacrolimus powder in Oraguard-B - A pilot prospective study - Upender Malik; Siddharth Gupta; Shilpa D. Malik; Shirin Vashishth; Zaheeruddin; M.S. Raju (Elsevier, 2012)
Objectives: The purpose of this study was to investigate the efficacy and safety of 0.1% tacrolimus powder in Oraguard-B for the treatment of patients with symptomatic oral lichen planus (OLP). Methods: This was a nonrandomized, nonblinded study conducted in the outpatient department. The 20 patients with symptomatic OLP oral lichen planus who were asked to participate in the study were provided with 20-g containers of the study medication. Patients were asked to use the medication over the symptomatic areas three times a day until resolution of the lesion. Patients were recalled to assess the drug response every 15 days. Results: The duration of treatment ranged from 30 to 183 days, with a mean of 81.8 ± 44.4 days; all 20 patients reported a favourable response to the topical tacrolimus therapy. Eleven patients had complete resolution of their lesions. In 16 of 20 patients, there was marked resolution in symptoms as recorded by visual analogue scale. Out of 10 patients followed up for a period of 3 months, 5 had recurrence of their lesions but with less intensity, and the patients were symptomless. No serious side effects were associated with the study medication. Conclusion: Topical tacrolimus 0.1% in Oraguard-B was effective and safe in treating patients with OLP. However, there is still a need to undertake more detailed and objective clinical studies to determine the exact benefit of tacrolimus compared with conventional therapies and examine the influence of different dose regimes and formulations and assess the incidence of recurrence. Keywords: Oral lichen planus, Topical tacrolimus, Oraguard-B